(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: This study investigates passive muscle stiffness assessed using Shear Wave Elastography (SWE), providing valuable insights into the mechanical properties of skeletal muscle and its relationship with neuromuscular control and rehabilitation. Our work presents an innovative approach by analyzing the passive stiffness of the rectus femoris and vastus lateralis muscles in different joint positions, using SWE to quantify regional changes and their biomechanical implications. The findings of this study suggest that muscle stiffness is not uniform and responds differently to variations in knee and hip position. Furthermore, the results indicate that changes in muscle stiffness may influence load distribution and joint function, which are crucial aspects for injury treatment and prevention. OBJETIVOS: 1) Assess the passive stiffness of RF and VL at two knee flexion angles (60 and 20) and in two body positions (supine and sitting) using SWE. 2) Evaluate passive stiffness variations at different muscle depths. 3) Investigate differences in passive stiffness between males and females. We hypothesized that greater passive stiffness would be observed in the supine with 60 knee flexion position, with no heterogeneity in stiffness along muscle depth and differences between sexes. MÉTODOS: Materials and Methods Study Design This was a randomized, crossover, and experimental trial approved by the Research Ethics Committee of the University of Brasília/Faculty of Ceilândia (protocol number 68446223.2.0000.8093), in accordance with the Declaration of Helsinki. All participants provided written informed consent prior to participation. Participants A total of 36 healthy individuals (18 men and 18 women) participated in the study. The sample had a mean age of 21.9 ± 3.0 years, height of 1.60 ± 0.01 m, and body mass of 66.8 ± 11.0 kg. All participants were classified as eutrophic (BMI: 18.5–24.9 kg/m2) and had not engaged in systematic lower limb strength training for at least six months. Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ), ensuring that all participants were physically active through recreational or sports activities. Randomization and Blinding Participants were randomly assigned to four testing conditions: SUP60 (supine with the knee at 60), SUP20 (supine with the knee at 20), SIT60 (sitting with the knee at 60), and SIT20 (sitting with the knee at 20). Randomization was performed using computer-generated sequences (www.random.org), and assignments were concealed in sealed, opaque, and sequentially numbered envelopes, opened in order upon participant enrollment. Participants were blinded to the study hypotheses and joint angle sequences. However, due to the nature of the testing positions, evaluator blinding was not feasible. Procedures During the familiarization session, participants underwent anthropometric assessments and eligibility screening. The rectus femoris (RF) and vastus lateralis (VL) muscles were selected to evaluate the stiffness behavior of biarticular (RF) and monoarticular (VL) components of the quadriceps. All assessments were conducted using an isometric dynamometer (IsoSystem 2.0, Cefise, Brazil), with participants positioned and stabilized according to each of the four joint configurations. Shear Wave Elastography (SWE) Passive muscle stiffness of the RF and VL was assessed using shear wave elastography (SWE), measuring both shear wave velocity (m/s) and stiffness (kPa), with the ACUSON Redwood ultrasound system (Siemens, USA). Measurements were taken at 50% of thigh length for the RF and 60% for the VL (from the anterior superior iliac spine to the base of the patella). A linear transducer (10–L4 MHz) was used to capture B-mode ultrasound images, and 30 circular regions of interest (ROIs) were manually selected per image—10 from each of the superficial, intermediate, and deep muscle regions. Muscle stiffness was determined by averaging shear modulus values from three images per muscle per position. A water-soluble gel was applied to the transducer to ensure proper acoustic coupling without exerting additional pressure. The assessment room was kept at a constant temperature (23–25 grau C) to avoid fluctuations in muscle stiffness. All measurements were performed by the same evaluator. Images were captured with participants at rest after a 10-second stabilization period. Shear wave velocity (m/s) was reported as the primary outcome, while stiffness values in kilopascals (kPa) were provided as supplementary data. RESULTADOS: Results Shear Wave Velocity (SWE, m/s) A significant interaction was found between muscle and position for SWE (p < 0.001). Post hoc analysis revealed that the supine position at 60 (SUP60) showed the highest SWE values for both the rectus femoris (RF) and vastus lateralis (VL) muscles compared to all other conditions. For RF, SWE was significantly greater in SUP60 (1.98 m/s) compared to SUP20 (1.60 m/s), SIT60 (1.63 m/s), and SIT20 (1.49 m/s) (all p < 0.001). Additionally, SUP20 showed higher values than SIT20 (p < 0.001), while SIT60 also exhibited greater SWE than SIT20 (p < 0.001). For VL, SUP60 again had the highest SWE (1.75 m/s), significantly greater than SUP20 (1.53 m/s), SIT60 (1.67 m/s), and SIT20 (1.44 m/s) (p < 0.001 for all comparisons). SIT60 values were also significantly higher than SIT20 and SUP20 (p < 0.001). Position × Depth Levels There was a significant interaction between position and muscle depth (superficial, intermediate, deep) for SWE (p < 0.001). SWE values were highest in the SUP60 position at all depth levels, especially in the superficial layer (1.99 m/s). Compared to SUP20, SIT60, and SIT20, SUP60 consistently demonstrated significantly greater SWE at superficial, intermediate, and deep regions (all p < 0.001). Within SUP60, the superficial layer showed higher SWE than intermediate and deep layers (p < 0.001). SUP20 also showed a decreasing trend in SWE from superficial to deep. SIT60 presented moderate SWE values, higher than SIT20 in all regions. SIT20 consistently had the lowest SWE values among all positions and levels. Sex Differences When considering sex as a factor, men exhibited significantly higher SWE values (1.70 m/s) compared to women (1.56 m/s) (p < 0.001), regardless of position or muscle. Measurement Reliability Intra-rater reliability was good to excellent for both RF and VL. For RF, intraclass correlation coefficients (ICCs) ranged from 0.80 (SIT20) to 0.88 (SUP60). For VL, reliability was excellent in SUP60 and SUP20 (ICC = 0.91), and good in SIT60 (0.81) and SIT20 (0.82). CONCLUSÕES: The findings revealed that quadriceps femoris exhibits non-uniform stiffness across different joint positions, muscle depths, and sexes. Higher stiffness was observed in the SUP60 position for both the RF and VL, and superficial regions consistently showed greater stiffness than deeper regions along with men displayed higher stiffness values compared to women. Clinicians should consider joint position, muscle depth, and sex differences when recommending quadriceps femoris exercises, as these factors influence the mapping and modulation of muscle stiffness. IMPLICAÇÕES: Implications of the Study This study on muscle stiffness assessed via shear wave elastography (SWE) provides important insights for clinical practice, sports medicine, and rehabilitation research. The main findings carry several implications: 1. Influence of Joint Position on Muscle Stiffness The study showed that the SUP60 position (supine with 60° knee flexion) led to the highest passive stiffness in both the rectus femoris (RF) and vastus lateralis (VL) muscles. This suggests that more flexed joint angles and a supine body position increase passive muscle tension, particularly in the RF, which spans two joints. Clinical implication: Evaluations of muscle stiffness or therapeutic interventions (such as stretching or mobilization) should account for both joint angle and body position. For example, to emphasize the stretch or activation of stiffer quadriceps regions, using the SUP60 position may be more effective. 2. Regional Differences Within Muscles The study found that the superficial regions of the muscles consistently showed significantly greater stiffness than the intermediate and deep regions, regardless of position or joint angle. Clinical implication: This suggests that interventions such as myofascial release, massage techniques, or even electrical stimulation should consider target tissue depth. Techniques targeting superficial layers may be more relevant when addressing areas of higher stiffness. 3. Differences Between RF and VL Muscles Although both muscles responded similarly to changes in positioning, the RF, due to its biarticular nature (acting on both the hip and knee), showed greater sensitivity to positional changes. The VL, being monoarticular, exhibited a more stable pattern. Functional implication: When designing strength or rehabilitation exercises, considering the biomechanical differences between biarticular and monoarticular muscles can help improve movement planning and reduce injury risk. 4. Influence of Sex Men demonstrated significantly greater passive stiffness than women, even after statistical adjustments. Clinical and athletic implication: This highlights the importance of sex-specific evaluation and intervention protocols, especially in contexts such as injury prevention, exercise prescription, or biomechanical assessments. 5. Applications in Rehabilitation and Performance The study’s findings are useful for physical therapists and trainers aiming to prescribe more precise exercises based on joint positioning and individual differences. Additionally, they provide a basis for standardized SWE protocols for assessing muscle stiffness.